African swine fever virus – persistence in different environmental conditions and the possibility of its indirect transmission - Mazur-Panasiuk Natalia (Journal of Veterinary Research, 2019)
Since 2007, African swine fever (ASF) has posed a serious threat to the European swine industry. In Poland, the numbers of reported outbreaks in pigs and affected areas grow every year. In 2018, the disease was noted in Western Europe, in Belgium specifically, where several hundred infected wild boars have been detected so far. In 2018, the virus unexpectedly emerged in pig holdings in eastern China, northern Mongolia, Vietnam, and Cambodia, causing worldwide concern about its further spread. Since there is still no vaccine available, the only approach to control the disease is biosecurity. Identification of potential sources of the virus is extremely important in light of its phenomenal survivability. The review summarises the current knowledge about ASFV survivability and resistance to environmental conditions, and discusses the role of indirect contact in spreading the disease.